High-speed experimental investigations on supersonic jet flows - Loon, Amos Yao Liang (2017)
One major concern regarding supersonic jets, particularly in its application to commercial aircraft, is the level of noise emissions. As such, much research has been devoted to studying the noise generating mechanisms of supersonic jets and the various methods to reduce the level of noise emissions. It is well known amongst researchers that there are 3 main noise components of supersonic jets, namely the turbulent mixing noise, the broadband shock-associated noise and the screech tones. As these 3 components are all strongly affected by the flow characteristics of the jet, altering the flow characteristics would have impacts on the jet noise emissions. One of the most practical and cost effective ways of altering the flow characteristics is to change the trailing edge geometry of the nozzle. This report aims to analyze the flow characteristics of 7 different nozzle trailing edge geometries using Schlieren Visualisation Techniques and Pitot Tube Measurements, which provide qualitative and quantitative results respectively. From the results, it was clear that the A-notched nozzles as well as the 60° Beveled nozzle had a much shorter potential core length when compared to the baseline circular nozzle, which implies the presence of enhanced mixing in the flow. Enhanced mixing has been known to help reduce supersonic jet noise emissions. Most of the asymmetrical nozzles showed a deflection of the jet exhaust at imperfectly-expanded conditions. Since turbulent mixing noise is highly directional, these deflections could result in a reduction of turbulent mixing noise in certain polar angles downstream of the nozzle. Furthermore, the asymmetrical nozzles exhibited asymmetrical quasi-periodic shock cell structures. This could result in differences in the shock-associated noise.